The influence of maternal diet on intestinal adaptation in the mother and offspring - Astbury, Stuart M. (2016)
The effect of maternal nutrition on fetal and offspring growth and risk of disease in later life is well established. Animal models have shown that the small intestine can be preferentially affected by growth restriction compared with other organs, yet the effect of maternal diet on gastrointestinal (GI) development has not been well studied. Furthermore, both the maternal GI tract and microbiome undergo significant adaptations during pregnancy in response to the increased nutritional demands of the growing fetus, which may be further modulated by the maternal diet.